“Deixa meu sangue escorrer”: como as visualidades operam sobre os sentidos da menstruação? - Gomides, Lana de Araújo (2020)
The main direction of this research is an approach of the visualities that operate on the menstruation senses. This clipping has to do with the cultural constructions that western society has undertaken over the centuries on the notions of gender and sexualities of the subjects. Official discourses are disseminated under the protection of different pedagogical forms that act, from the terminological perspective of Michel Foucault (1999), as a network of devices in order to control the behavior of society. The woman saw herself framed in social roles imposed by the sexist and misogynistic hegemonic hand, and her body still carries marks of a path sustained by naturalized ideas. In this sense, menstruation is presented, in different situations, as a physical and emotional barrier due to the taboos assigned to it. Once the advertisement images were, for a long time, the main form of public exposure of the theme, the dialogue proposed here has them as the entry point to carry out transits in the field of Visual Culture Studies. To understand the popular imagination, as well as the nuances that permeate the actions of those who occupy positions of power, this writing dialogued with visualities produced by absorbent and analgesic brands that propose to relieve the pains arising out from menstrual cramps. After the conclusion of the first chapter, the research approaches itself to the contravisualities resulting from the non-acceptance of the official speeches. The discussion support is in the works of artists who, from menstruation, provoked reflections on the senses that were attributed to the female body. The third chapter makes contact with the experiences of women and of a transsexual man who carry, in their bodies, place of speech in relation to the subject. Far from reaching a final conclusion and establishing truths, the aim of this search is to provoke the displacement of the gaze towards the visualities to which we are exposed and cause weirdities towards such normalities.